Unpacking the relationship between high-performance work systems and innovation performance in SMEs. Issue 4 (2nd May 2019) - Shahzad, Khuram; Arenius, Pia; Muller, Alan; Rasheed, Muhammad Athar; Bajwa, Sami Ullah
Abstract : Purpose: The purpose of this paper is to explore the black box between high-performance work systems (HPWS) and innovation performance in small- and medium-sized enterprises (SMEs). Through application of the ability, motivation and opportunity (AMO) framework, the study examines the mediating roles of innovation-specific ability, motivation and voice behaviors between HPWS and SMEs' innovation performance. Design/methodology/approach: The hypotheses are tested on data collected through a self-administered questionnaire from 237 SMEs in Pakistan. Findings: Findings indicate that human capital, motivation and employee voice fully mediate the relationship between HPWS and innovation performance in SMEs. Research limitations/implications: The cross-sectional research design and self-reported measures warrant caution for the interpretation of findings. Future research may consider a longitudinal research design and objective measures. Practical implications: SMEs need to invest in the adoption and implementation of HPWS that will develop innovation-specific abilities, motivation and voice behaviors simultaneously among employees that will lead to higher innovation performance. Originality/value: This is the first study of its kind utilizing an AMO framework to investigate the underlying mechanism through which HPWS affect innovation performance in SMEs.